P0974ADIPORON AMELIORATES DIABETIC CARDIOMYOPATHY IN DBDB MICE THROUGH IMPROVING CERAMIDE-DEPENDENT LIPOTOXICITY. (6th June 2020) - Kim, Yaeni; Lim, Ji Hee; Kim, Eun Nim; JIN, YONGJIE; Kim, Hyung Duk; Ban, Tae Hyun; Choi, Bum Soon; Park, Cheol Whee
Abstract: Background and Aims: The accumulation of lipid and its metabolites in tissues, including the heart, causes lipotoxicity. Sphingolipids such as ceramides are particularly deleterious. Lowering the accumulation of ceramide can improve metabolic damage of various tissues. Recent reports showed that adiponectin receptors (AdipoRs) have sequence homology with ceramidase enzymes, and an increase of ceramidase activity with overexpression of adiponectin in mice improves ceramide-dependent lipotoxicity. Therefore, we investigated the possible roles of Adiporon, which mimics the effects of adiponectin, in the view of prevention and development of diabetic cardiomyopathy in diabetic mouse model. Method: Male db/db mice and db/m controls were fed either a regular diet chow or a diet containing adiporon (30 mg/kg/day p.o. for 4 weeks from 17 to 20 weeks of age) and biochemical and morphological parameters were examined at 20 weeks of age. Results: In db/db mice, left ventricular developed pressure (LVDP), heart rate (HR) and coronary flow rate (CFR) were decreased compared to db/m control mice, indicating cardiovascular dysfunction in diabetic heart. The treatment with AdipoRon remarkably improved the diabetes-induced contractile impairment, without any influence on HR. Adioporon also decreased fibrosis, inflammation cell infiltration and accumulations of free fatty acid, triglycerides and ceramide in the heart. In the molecular level, increased expressions of AdipoR1 and AdipoR2 and acid ceramidase activity in the heart were observed in db/db mice with Adiporon administration. Consistent up-regulations of phosphorylated AMPK and PPAR-α level were associated within the same group. Subsequent improvement of enhanced lipid metabolism and decrement of cellular apoptosis with adiporon treatment were also noted. Conclusion: Adiporon may control oxidative stress in heart through AMPK and PPAR-α activated pathway and further contribute to prevent deterioration of cardiac function. The protective role of adiporon against the development of diabetic cardiomyopathy seems to occur through a direct action on the heart independently of systemic effects of adiponectin. Our results suggest adiporon as a promising therapeutic agent of diabetic cardiomyopathy through ameliorating ceramide-dependent lipotoxicity.